"Prvič, sem političarka in ne politik, drugič pa --- " - Fišer, Darja (Prispevki za novejšo zgodovino, 2021)
This tutorial shows how corpora can be used to investigate language use and communication practices in a specialized socio-cultural context of political discourse in order to explore socio-cultural phenomena. We will demonstrate the potential of a richly annotated diachronic corpus of Slovenian parliamentary debates for investigating the characteristics and dynamics of the representation of women and their language use in the Slovenian Parliament.
Keywords: digitalna humanistika; jezik in spol; parlamentarne razprave; parlamentarni korpusi